Hardmetal and cutting tools

The carbide alloy, with its high tungsten carbide content and specific bonding phase composition, addresses the challenge of short tool life in printed circuit board drilling by enhancing the tool's strength and wear resistance.

JP7670234B1Active Publication Date: 2025-04-30SUMITOMO ELECTRIC INDUSTRIES LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2024516661
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2023-09-26
Publication Date
2025-04-30
Estimated Expiration
2043-09-26

AI Technical Summary

Technical Problem

Cutting tools used for drilling holes in printed circuit boards experience increased wear and breakage due to the higher heat resistance demands, leading to shorter tool life.

Method used

A carbide alloy comprising a high volume percentage of tungsten carbide particles and a bonding phase with 40% or more cobalt content, along with specific elements like silicon, phosphorus, and platinum, which are not segregated at the interface regions, enhancing the alloy's strength and wear resistance.

Benefits of technology

The carbide alloy significantly extends the life of cutting tools, particularly when used for drilling printed circuit boards, by improving the tool's hardness, toughness, and resistance to wear and breakage.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007670234000006
    Figure 0007670234000006
  • Figure 0007670234000007
    Figure 0007670234000007
  • Figure 0007670234000008
    Figure 0007670234000008
Patent Text Reader

Abstract

A cemented carbide alloy comprising a plurality of tungsten carbide particles and a binder phase, the cemented carbide alloy comprising a total of 89 volume % or more of the tungsten carbide particles and the binder phase, the cemented carbide alloy comprising 1.5 volume % or more and 23 volume % or less of the binder phase, the binder phase comprising 40 mass % or more of cobalt, the binder phase further comprising at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum, the first element not segregating in a first interface region between adjacent tungsten carbide particles, and the first element not segregating in a second interface region between adjacent tungsten carbide particles and the binder phase.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to hardmetals and cutting tools. [Background technology]

[0002] Conventionally, cemented carbide having a plurality of tungsten carbide particles and a binder phase has been used as a material for cutting tools (Patent Document 1). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2004-131769 A Summary of the Invention

[0004] The cemented carbide of the present disclosure is A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 89% by volume or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 1.5% by volume or more and 23% by volume or less of the binder phase, The binder phase contains 40% by mass or more of cobalt, the binder phase further comprises at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum; The first element is not segregated in a first interface region between adjacent tungsten carbide particles, and The cemented carbide is a hard alloy, wherein the first element does not segregate in a second interface region between adjacent tungsten carbide particles and the binder phase. [Brief description of the drawings]

[0005] [Figure 1] FIG. 1 is a schematic cross-sectional view of a cemented carbide according to a first embodiment. [Diagram 2] FIG. 2 is a diagram showing an example of a first image of the cemented carbide according to the first embodiment. [Diagram 3] FIG. 3 is a diagram for explaining a method for confirming that the first element is not segregated in the first interface region, and shows a first graph. [Figure 4] FIG. 4 is a diagram for explaining a method for confirming that the first element is not segregated in the second interface region, and shows a second graph. [Diagram 5] FIG. 5 is a schematic diagram of a cutting tool according to the second embodiment. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0006] [Problem that this disclosure aims to solve] In recent years, work materials have become increasingly difficult to cut in cutting processes, and the conditions for using cutting tools have become harsher. For example, in the case of printed circuit boards, with the expansion of 5G (fifth generation mobile communication systems), the amount of information is increasing, and further heat resistance is required for printed circuit boards. In order to improve the heat resistance of printed circuit boards, technologies have been developed to improve the heat resistance of the resin and glass filler that make up the printed circuit board. However, this has made printed circuit boards increasingly difficult to cut. For this reason, cutting tools tend to be easily worn or broken when processing printed circuit boards.

[0007] Therefore, an object of the present disclosure is to provide a cemented carbide alloy that enables a longer service life of a cutting tool, particularly when used as a material for the cutting tool for drilling holes in printed circuit boards, and a cutting tool equipped with the same.

[0008] [Effects of this disclosure] According to the present disclosure, it is possible to provide a cemented carbide alloy and a cutting tool having the same that enable a longer life of the cutting tool, particularly when the cutting tool is used as a material for drilling holes in printed circuit boards.

[0009] [Description of the embodiments of the present disclosure] First, the embodiments of the present disclosure will be listed and described. (1) The cemented carbide disclosed herein is A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 89% by volume or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 1.5% by volume or more and 23% by volume or less of the binder phase, The binder phase contains 40% by mass or more of cobalt, the binder phase further comprises at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum; The first element is not segregated in a first interface region between adjacent tungsten carbide particles, and The cemented carbide is a hard alloy, wherein the first element does not segregate in a second interface region between adjacent tungsten carbide particles and the binder phase.

[0010] According to the present disclosure, it is possible to provide a cemented carbide that enables a longer life of cutting tools, particularly when used as a material for cutting tools for drilling holes in printed circuit boards.

[0011] (2) In the above (1), the percentage of the mass M1 of the first element in the binder phase to the sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt, {M1 / (M1+M2)}×100, may be 1% or more and 6% or less. Here, the units of the mass M1 and the mass M2 are the same. This makes it possible to provide a cemented carbide that can extend the tool life of a cutting tool.

[0012] (3) In (1) or (2) above, The cemented carbide is an intermetallic compound consisting of two or more elements selected from the group consisting of the first element, cobalt, and tungsten; and The first element may not include a first compound consisting of at least one element selected from the group consisting of cobalt and tungsten, and at least one element selected from the group consisting of carbon, nitrogen, and oxygen. Here, the first compound does not include tungsten carbide.

[0013] This suppresses the decrease in strength of the cemented carbide.

[0014] (4) A cutting tool according to the present disclosure is a cutting tool having a cutting edge made of the cemented carbide according to any one of (1) to (3) above.

[0015] This makes it possible to provide a cutting tool that has a long tool life, especially when used for drilling holes in printed circuit boards.

[0016] [Details of the embodiment of the present disclosure] Specific examples of the cemented carbide and cutting tool of the present disclosure will be described below with reference to the drawings. In the drawings of the present disclosure, the same reference numerals represent the same or corresponding parts. Furthermore, dimensional relationships such as length, width, thickness, and depth have been appropriately changed for clarity and simplification of the drawings, and do not necessarily represent actual dimensional relationships.

[0017] In this disclosure, an expression in the form "A to B" means the upper and lower limits of a range (i.e., A or more and B or less). When no unit is specified for A and a unit is specified only for B, the unit of A and the unit of B are the same.

[0018] In the present disclosure, when a compound or the like is represented by a chemical formula, unless the atomic ratio is particularly limited, it is intended to include any conventionally known atomic ratio, and should not necessarily be limited to only those within the stoichiometric range.

[0019] In the present disclosure, when one or more numerical values ​​are described as the lower limit and the upper limit of a numerical range, a combination of any one numerical value described as the lower limit and any one numerical value described as the upper limit is also disclosed. For example, when a1 or more, b1 or more, and c1 or more are described as the lower limit, and a2 or less, b2 or less, and c2 or less are described as the upper limit, a1 or more and a2 or less, a1 or more and b2 or less, a1 or more and c2 or less, b1 or more and a2 or less, b1 or more and b2 or less, b1 or more and c2 or less, c1 or more and a2 or less, c1 or more and b2 or less, and c1 or more and c2 or less are disclosed.

[0020] [Embodiment 1: Carbide] A cemented carbide according to one embodiment of the present disclosure will be described with reference to FIG. The cemented carbide 3 according to one embodiment of the present disclosure (hereinafter also referred to as "embodiment 1") is A cemented carbide (3) comprising a plurality of tungsten carbide particles (1) and a binder phase (2), The cemented carbide 3 contains tungsten carbide particles 1 and a binder phase 2 in a total amount of 89 volume % or more, The cemented carbide 3 contains a binder phase 2 of 1.5 volume % or more and 23 volume % or less, The binder phase 2 contains 40% by mass or more of cobalt, The bonding phase 2 further contains at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum; In a first interface region between adjacent tungsten carbide particles 1, the first element is not segregated, and The cemented carbide 3 has a second interface region between adjacent tungsten carbide particles 1 and a binder phase 2, in which the first element does not segregate.

[0021] The cemented carbide of embodiment 1 can provide a cemented carbide that enables a cutting tool to have a longer life, particularly when used as a material for the cutting tool used to drill holes in printed circuit boards, and a cutting tool including the same. The reason for this is not clear, but is presumed to be as follows.

[0022] The cemented carbide of the first embodiment comprises a plurality of tungsten carbide particles (hereinafter also referred to as "WC particles") and a binder phase, and the total content of the WC particles and the binder phase in the cemented carbide is 89 volume % or more. As a result, the cemented carbide has high hardness and strength, and a cutting tool comprising the cemented carbide can have excellent wear resistance and breakage resistance.

[0023] The cemented carbide of the first embodiment contains a binder phase of 1.5% by volume or more and 23% by volume or less, and the binder phase contains 40% by mass or more of cobalt. Thus, the cemented carbide has high hardness and strength, and a cutting tool including the cemented carbide can have excellent wear resistance and breakage resistance.

[0024] In the cemented carbide of the first embodiment, the binder phase contains at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum. Furthermore, the first element does not segregate in the first interface region between adjacent tungsten carbide particles, and the first element does not segregate in the second interface region between adjacent tungsten carbide particles and the binder phase. This further improves the interface strength between the tungsten carbide particles in the cemented carbide, and the interface strength between the tungsten carbide particles and the binder phase, and suppresses the detachment of the tungsten carbide particles during cutting. Therefore, a cutting tool using the cemented carbide as a material can have a long tool life. Furthermore, the hole position accuracy of the cutting tool is also improved.

[0025] <Composition of cemented carbide> The cemented carbide of the first embodiment contains tungsten carbide particles and a binder phase in a total amount of 89% or more by volume. This can increase the hardness of the cemented carbide. The cemented carbide may contain tungsten carbide particles and a binder phase in a total amount of 89% to 100% by volume, 90% to 100% by volume, 91% to 100% by volume, or 92% to 100% by volume.

[0026] The cemented carbide of the first embodiment contains 1.5 to 23 volume % of a binder phase. This can increase the hardness and toughness of the cemented carbide. The content of the binder phase in the cemented carbide may be 2.0 to 19.0 volume %, 3.0 to 18.0 volume %, or 4.0 to 17.0 volume %.

[0027] The cemented carbide of the first embodiment may be composed of a plurality of tungsten carbide particles and a binder phase. In this case, the cemented carbide may contain impurities within a range that does not impair the effects of the present disclosure.

[0028] The cemented carbide may contain other phases (not shown) in addition to the tungsten carbide particles and binder phase. The other phases may include carbides, nitrides, or carbonitrides containing at least one element selected from the group consisting of titanium (Ti), tantalum (Ta), niobium (Nb), zirconium (Zr), hafnium (Hf), and molybdenum (Mo). The composition of the other phases may be, for example, at least one selected from the group consisting of TiCN, TaC, NbC, ZrC, HfC, and Mo2C.

[0029] The cemented carbide of the first embodiment may be composed of tungsten carbide particles, a binder phase, and other phases. In this case, the cemented carbide may contain impurities as long as the effects of the present disclosure are not impaired.

[0030] The content of other phases in the cemented carbide is permitted within a range that does not impair the effects of the present disclosure. For example, the content of other phases in the cemented carbide may be more than 0 vol% and not more than 11 vol%, more than 0 vol% and not more than 7 vol%, or more than 0 vol% and not more than 4 vol%.

[0031] The cemented carbide of the first embodiment may contain impurities. Examples of impurities include iron (Fe), calcium (Ca), silicon (Si), and sulfur (S). The content of impurities in the cemented carbide is permissible within a range that does not impair the effects of the present disclosure. For example, the content of impurities in the cemented carbide may be 0% by mass or more and less than 0.1% by mass. The content of impurities in the cemented carbide is measured by ICP optical emission spectroscopy (Inductively Coupled Plasma Emission Spectroscopy). The measurement device that can be used is Shimadzu Corporation's "ICPS-8100" (trademark).

[0032] The content of tungsten carbide particles in the cemented carbide of embodiment 1 may be 67 vol. % to 98.5 vol. %, 70 vol. % to 97 vol. %, or 75 vol. % to 96 vol. %.

[0033] The method for measuring the content (volume %) of tungsten carbide particles in the cemented carbide and the content (volume %) of the binder phase in the cemented carbide is as follows.

[0034] (A1) An arbitrary position of the cemented carbide is cut out to expose a cross section, which is then mirror-finished using a cross-section polisher (manufactured by JEOL Ltd.).

[0035] (B1) The mirror-finished surface of the cemented carbide is analyzed using an energy dispersive X-ray spectrometer (SEM-EDX) attached to a scanning electron microscope (Apparatus: Carl Zeiss Gemini450 (trademark)) to identify the elements contained in the cemented carbide.

[0036] (C1) The mirror-finished surface of the cemented carbide is photographed with a scanning electron microscope (SEM) to obtain a backscattered electron image. The photographed area is set to the center of the cemented carbide cross section, that is, a position that does not include areas with properties that are clearly different from the bulk part, such as the surface area of ​​the cemented carbide (a position where the photographed area is entirely the bulk part of the cemented carbide). The observation magnification is 5000x. The measurement conditions are an acceleration voltage of 3kV, a current value of 2nA, and a working distance (WD) of 5mm.

[0037] (D1) The photographed region of (C1) above is analyzed using SEM-EDX to identify the distribution of the elements identified in (B1) above in the photographed region, and an element mapping image is obtained.

[0038] (E1) The backscattered electron image obtained in (C1) above is imported into a computer and binarized using image analysis software (OpenCV, SciPy). In the binarized image, tungsten carbide particles are shown in white, and the bond phase is shown in gray to black. Note that the binarization threshold changes depending on the contrast, so it is set for each image.

[0039] (F1) By superimposing the element mapping image obtained in (D1) above and the image after the binarization process obtained in (E1) above, the respective regions of the tungsten carbide particles and the binder phase are identified on the image after the binarization process. Specifically, the regions shown in white in the image after the binarization process and in which tungsten (W) and carbon (C) exist in the element mapping image correspond to the regions of the tungsten carbide particles. The regions shown in gray to black in the image after the binarization process and in which cobalt (Co) exists in the element mapping image correspond to the regions of the binder phase.

[0040] (G1) A rectangular measurement field of view of 24.9 μm × 18.8 μm is set in the image after the binarization process. Using the image analysis software, the area percentages of the tungsten carbide particles and the binder phase are measured with the area of ​​the entire measurement field as the denominator.

[0041] (H1) The measurement of (G1) above is carried out in five different non-overlapping measurement fields. In the present disclosure, the average of the area percentages of tungsten carbide particles in the five measurement fields corresponds to the content (volume %) of tungsten carbide particles in the cemented carbide, and the average of the area percentages of the binder phase in the five measurement fields corresponds to the content (volume %) of the binder phase in the cemented carbide.

[0042] If the cemented carbide contains other phases in addition to the WC particles and the binder phase, the content of the other phases in the cemented carbide can be obtained by subtracting the content (volume %) of the tungsten carbide particles and the content (volume %) of the binder phase measured by the above procedure from the total cemented carbide (100 volume %).

[0043] As long as the measurements are performed on the same sample, it has been confirmed that there is almost no variation in the measurement results even if the cut-out location of the cross section of the cemented carbide, the photographing area described in (C1) above, and the measurement field of view described in (G1) above are arbitrarily set and the tungsten carbide particle content and binder phase content of the cemented carbide are measured multiple times according to the above procedure.

[0044] The cobalt content of the cemented carbide of embodiment 1 may be 1.0 mass % or more and 20 mass % or less, 2.0 mass % or more and 15 mass % or less, or 3.0 mass % or more and 12 mass % or less.

[0045] The method for measuring the cobalt content of the cemented carbide is as follows. Analysis is performed using SEM-EDX in the same manner as (A1) to (D1) of the method for measuring the tungsten carbide particle content and the binder phase content of the cemented carbide to obtain an element mapping image. Based on the element mapping image, the cobalt region in the cemented carbide is identified, and the cobalt content is measured. The measurement is performed in five different non-overlapping imaging regions. In the present disclosure, the average of the cobalt contents in the five imaging regions corresponds to the cobalt content of the cemented carbide.

[0046] As long as the measurements were performed on the same sample, it was confirmed that there was almost no variation in the measurement results even if the cut-out location of the cross section of the cemented carbide and the photographing area described in (C1) above were arbitrarily set and the cobalt content of the cemented carbide was measured multiple times according to the above procedure.

[0047] <Tungsten carbide particles> In the cemented carbide of the first embodiment, the tungsten carbide particles include at least one of "pure WC particles (including WC containing no impurity elements and WC containing impurity elements below the detection limit)" and "WC particles containing impurity elements intentionally or unavoidably, as long as the effect of the present disclosure is not impaired." The content of impurities in the tungsten carbide particles (when two or more elements are included as impurities, the total concentration of the elements) is less than 0.1% by mass. The content of impurities in the tungsten carbide particles is measured by ICP emission spectrometry.

[0048] In the first embodiment, the average particle size of the tungsten carbide particles is not particularly limited. The average particle size of the tungsten carbide particles can be, for example, 0.1 μm or more and 3.5 μm or less. It has been confirmed that the cemented carbide of the first embodiment can extend the life of a cutting tool when used as a material for the cutting tool, regardless of the average particle size of the tungsten carbide particles.

[0049] <Binded phase> In the cemented carbide of embodiment 1, the binder phase contains 40% by mass or more of cobalt. This allows the cemented carbide to have excellent toughness. The cobalt content of the binder phase may be 40% by mass or more and less than 100% by mass, 50% by mass or more and 90% by mass or less, or 60% by mass or more and 80% by mass or less.

[0050] The method for measuring the cobalt content of the binder phase is as follows. An element mapping image and an image after binarization are obtained by the same method as (A1) to (E1) of the method for measuring the content of tungsten carbide particles and the content of the binder phase of the cemented carbide. The element mapping image and the image after binarization are superimposed to identify the region in which the binder phase exists in the element mapping image. A rectangular measurement field of view of 24.9 μm×18.8 μm is set in the element mapping image. The cobalt content is measured in the region in which the binder phase exists in the measurement field of view. The above measurement is performed in five different measurement fields that do not overlap each other. In the present disclosure, the average of the cobalt contents in the regions in which the binder phase exists in the five measurement fields of view corresponds to the cobalt content of the binder phase.

[0051] As long as the measurements are performed on the same sample, it has been confirmed that there is almost no variation in the measurement results even if the cut-out location of the cross section of the cemented carbide, the photographing area described in (C1) above, and the measurement field of view described above are arbitrarily set and the cobalt content of the binder phase is measured multiple times according to the above procedure.

[0052] In the cemented carbide of embodiment 1, the binder phase further comprises at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum.

[0053] The inclusion of the first element in the binder phase is confirmed by the following procedure. An element mapping image and a binarized image are obtained by the same methods as (A1) to (E1) of the above-mentioned method for measuring the tungsten carbide particle content and binder phase content of a cemented carbide alloy. The element mapping image and the binarized image are superimposed to identify the region in the element mapping image where the binder phase exists. Element Mapping image When the first element is present in the region where the binder phase is present, it is confirmed that the binder phase contains the first element.

[0054] In the binder phase of the cemented carbide of the first embodiment, the percentage {M1 / (M1+M2)}×100 of the mass M1 of the first element with respect to the total M1+M2 of the mass M1 of the first element and the mass M2 of cobalt may be 1% or more and 6% or less. Here, the units of the mass M1 and the mass M2 are the same. As a result, the binder phase can have both better hardness and better toughness, so that a cutting tool including the cemented carbide including the binder phase can have a longer tool life. Here, the mass M1 of the first element means the total mass of all the types of the first elements when the binder phase includes two or more types of the first elements. The percentage {M1 / (M1+M2)}×100 may be 2% or more and 5% or less, or 3% or more and 4% or less.

[0055] The method for measuring the percentage {M1 / (M1+M2)}×100 is as follows. An element mapping image and a binarized image are obtained by the same method as (A1) to (E1) of the method for measuring the content of tungsten carbide particles and the content of the binder phase of the cemented carbide. The element mapping image and the binarized image are superimposed to identify the region in which the binder phase exists in the element mapping image. A rectangular measurement field of view of 24.9 μm×18.8 μm is set in the element mapping image. In the region in which the binder phase exists in the measurement field of view, the percentage {m1 / (m1+m2)}×100 of the mass m1 of the first element relative to the sum m1+m2 of the mass m1 of the first element and the mass m2 of cobalt is calculated. The above measurement is performed in five different measurement fields of view that do not overlap each other. In the present disclosure, the average of the percentage {m1 / (m1+m2)}×100 in the five measurement fields corresponds to the "percentage {M1 / (M1+M2)}×100" in the binder phase of the cemented carbide.

[0056] As long as measurements were taken on the same sample, it was confirmed that there was almost no variation in the measurement results, even if the cut-out location of the cross section of the cemented carbide, the photographing area described in (C1) above, and the measurement field of view were arbitrarily set, and the percentage {M1 / (M1+M2)}×100 was measured multiple times according to the above procedure.

[0057] In the cemented carbide of the first embodiment, the binder phase may contain, in addition to cobalt and the first element, at least one second element selected from the group consisting of iron (Fe), nickel (Ni) and chromium (Cr). The binder phase may consist of cobalt, the first element and the second element. The binder phase may consist of cobalt, the first element, the second element and inevitable impurities. Examples of the inevitable impurities include iron (Fe), nickel (Ni) and sulfur (S).

[0058] <First interface region and second interface region> In the cemented carbide of embodiment 1, the first element is not segregated in the first interface region between adjacent tungsten carbide particles, and the first element is not segregated in the second interface region between adjacent tungsten carbide particles and a binder phase. This improves the interface strength between the tungsten carbide particles and between the tungsten carbide particles and the binder phase, thereby improving the wear resistance and breakage resistance of the cemented carbide.

[0059] In the present disclosure, a method for confirming that the first element is not segregated in the first interface region between adjacent tungsten carbide particles of the cemented carbide will be described with reference to Figs. 2 and 3 .

[0060] (A2) Using an argon ion slicer ("Cryo Ion Slicer IB-09060BCIS" (trademark) manufactured by JEOL Ltd.), the cemented carbide is sliced ​​to a thickness of 30 to 100 nm under conditions of an acceleration voltage of 6 kV and finishing voltage of 2 kV to prepare a measurement sample. The measurement sample is observed at 200,000 times magnification using a Transmission Electron Microscopy (TEM) ("JEM-ARM300F2" (trademark) manufactured by JEOL Ltd.) under conditions of an acceleration voltage of 200 V to obtain a first image. An example of the first image is shown in FIG. 2.

[0061] (B2) In the first image, the tungsten carbide particles 1 are observed as white to gray regions, the binder phase 2 is observed as black regions, and the interfaces 4 located between adjacent tungsten carbide particles 1 are observed as black regions. In the first image, the width of the interfaces 4 is, for example, 2 nm or less. In the first image, the interfaces between adjacent tungsten carbide particles are arbitrarily selected. Hereinafter, in the present disclosure, the adjacent tungsten carbide particles are also referred to as first tungsten carbide particles and second tungsten carbide particles.

[0062] (C2) Next, the selected interface is positioned so as to pass through the center of the image, and the observation magnification is adjusted so that the field of view size is 5 nm x 5 nm, and a second image is obtained. In the second image, the extension direction of the interface is confirmed. Line analysis is performed with an energy dispersive X-ray analyzer (TEM-EDX) attached to the TEM in a direction perpendicular to the extension direction and from the first tungsten carbide particle to the second tungsten carbide particle, and a graph (hereinafter also referred to as the first graph) is obtained in which the distribution of cobalt, tungsten, and the first element is measured. When the cemented carbide contains two or more types of the first element, the distribution of each element is measured. Here, the direction perpendicular to the extension direction of the interface means the direction along a straight line that intersects with the tangent of the extension direction at an angle of 90° ± 5°. For example, in FIG. 2, the direction indicated by the arrow corresponds to the direction perpendicular to the extension direction of the interface. The measurement conditions for acquiring the second image were an acceleration voltage of 200 kV, a camera length of 10 cm, a pixel count of 128 × 128 pixels, and a dwell time of 0.02 to 3 s / pixel.

[0063] Fig. 3 is an example of the first graph. In Fig. 3, the horizontal axis (X axis) indicates the distance (nm) from the measurement start point, and the vertical axis (Y axis) indicates the content (atomic %) of each element. In the cemented carbide shown in Fig. 3, the first element is silicon (Si).

[0064] (D2) In the first graph, the peak position of cobalt is identified. In this disclosure, the peak position of cobalt is referred to as the first interface. The first interface is formed between a first tungsten carbide particle and a second tungsten carbide particle adjacent to each other. In the first graph of FIG. 3, the first interface is located at 5.98 nm on the X-axis.

[0065] In the first graph, a first A region is identified in which the distance from the first interface to the first tungsten carbide particle side is within 1.20 nm, and a first B region is identified in which the distance from the first interface to the second tungsten carbide particle side is within 1.20 nm. In the present disclosure, the region consisting of the first A region and the first B region is the first interface region. In the first graph of FIG. 3, the first interface region is located in the region of 4.78 to 7.18 nm on the X-axis. In the present disclosure, the first interface region between adjacent tungsten carbide particles can also be expressed as a first interface region located between adjacent tungsten carbide particles.

[0066] In the first graph, a second A region is identified in which the distance from the first interface to the first tungsten carbide particle side is 1.50 nm or more and 3.50 nm or less, and a second B region is identified in which the distance from the first interface to the second tungsten carbide particle side is 1.50 nm or more and 3.50 nm or less. In the first graph of Fig. 3, the second A region is located in the region of 2.48 to 4.48 nm on the X axis, and the second B region is located in the region of 7.48 to 9.48 nm on the X axis.

[0067] (E2) Based on the first graph, calculate the average content B (atomic %) of the first element in the baseline region consisting of the second A region and the second B region. Measure the maximum content A (atomic %) of the first element in the first interface region in the first graph. When the ratio A / B of the maximum value A to the average B is less than 3, it is confirmed that the first element is not segregated in the first interface region between adjacent tungsten carbide particles of the cemented carbide.

[0068] In the first graph of Fig. 3, the average content B of silicon (first element) in the baseline region consisting of the 2A region and the 2B region is 7.68 atomic %, and the maximum content A of silicon (first element) in the first interface region is 6.75 atomic %. In the cemented carbide shown in Fig. 3, A / B is 0.9, so it is confirmed that the first element is not segregated in the first interface region between adjacent tungsten carbide particles of the cemented carbide.

[0069] (F2) In a cemented carbide, five mutually non-overlapping first images are arbitrarily obtained, a first graph is obtained based on each of the first images, and the above-mentioned analysis is repeatedly performed. If segregation of the first element is not confirmed in the first interface region in four or more of the first graphs, it is determined that the first element is not segregated in the first interface region between adjacent tungsten carbide particles of the cemented carbide.

[0070] In the present disclosure, a method for confirming that the first element is not segregated in the second interface region between adjacent tungsten carbide particles and the binder phase will be described with reference to FIG.

[0071] (A3) A first image is obtained in the first interface region by the same method as (A2) described in the method for confirming that the first element is not segregated in the first interface region. In the first image, an interface between adjacent tungsten carbide particles and a binder phase is arbitrarily selected.

[0072] (B3) Next, the selected interface is positioned so as to pass through the vicinity of the center of the image, and the observation magnification is adjusted so that the field of view size is 5 nm x 5 nm, and the third image is obtained. In the third image, the extension direction of the interface is confirmed. Line analysis is performed by TEM-EDX in a direction perpendicular to the extension direction and from the tungsten carbide particle toward the bonding phase, and a graph (hereinafter also referred to as the second graph) is obtained in which the distribution of cobalt, tungsten, and the first element is measured. When the cemented carbide contains two or more kinds of the first element, the distribution of each element is measured. Here, the direction perpendicular to the extension direction of the interface means the direction along a straight line that intersects with the tangent of the extension direction at an angle of 90° ± 5°. The measurement conditions when acquiring the third image are an acceleration voltage of 200 kV, a camera length of 10 cm, a pixel count of 128 x 128 pixels, and a dwell time of 0.02 to 3 s / pixel.

[0073] Fig. 4 is an example of the second graph. In Fig. 4, the horizontal axis (X axis) indicates the distance (nm) from the measurement start point, and the vertical axis (Y axis) indicates the content (atomic %) of each element. In the cemented carbide shown in Fig. 4, the first element is silicon (Si).

[0074] In the second graph, the position where the tungsten content and the cobalt content intersect is identified. In the present disclosure, the position where the tungsten content and the cobalt content intersect is referred to as the second interface. The second interface is formed between adjacent tungsten carbide particles and the binder phase. In the second graph of FIG. 4, the second interface is located at 5.97 nm on the X-axis.

[0075] In the second graph, a first C region is identified that is within 1.20 nm from the second interface to the tungsten carbide particle side, and a first D region is identified that is within 1.20 nm from the second interface to the binder phase side. In the present disclosure, the region consisting of the first C region and the first D region is the second interface region. In the second graph of FIG. 4, the second interface region is located in the region of 4.76 to 7.16 nm on the X-axis. In the present disclosure, the second interface region between the adjacent tungsten carbide particles and the binder phase can also be expressed as the second interface region located between the adjacent tungsten carbide particles and the binder phase.

[0076] In the second graph, from the second interface Carbonization A second C region having a distance to the tungsten particle side of 1.50 nm or more and 3.50 nm or less, and a second D region having a distance from the second interface to the bonding phase side of 1.50 nm or more and 3.50 nm or less are identified. In the second graph of Fig. 4, the second C region is located in the region of 2.46 to 4.46 nm on the X axis, and the second D region is located in the region of 7.46 to 9.46 nm on the X axis.

[0077] Based on the second graph, the average content D (atomic %) of the first element in the baseline region consisting of the second C region and the second D region is calculated. In the second graph, the maximum content C (atomic %) of the first element in the second interface region is measured. When the ratio C / D of the maximum value C to the average D is less than 3, it is confirmed that the first element is not segregated in the second interface region between the adjacent tungsten carbide particles and the binder phase of the cemented carbide.

[0078] (C3) In a cemented carbide, five mutually non-overlapping first images are arbitrarily obtained, a second graph is obtained based on each of the first images, and the above-mentioned analysis is repeatedly performed. If segregation of the first element is not confirmed in the second interface region in four or more of the second graphs, it is determined that the first element is not segregated in the second interface region between adjacent tungsten carbide particles and a binder phase in the cemented carbide.

[0079] As long as the same sample is measured, the cut-out portion of the cemented carbide cross section is arbitrarily set, the first image is arbitrarily obtained on the cross section, and the presence or absence of segregation of the first element in the first interface region and the second interface region is confirmed to have almost no variation in the results of the presence or absence of segregation of the first element in the first interface region and the second interface region, even if the line analysis region is changed and the confirmation is performed multiple times according to the above procedure. Therefore, as long as the above method for confirming the segregation of the first element is performed on the cemented carbide and it is confirmed that the first element is not segregated in the first interface region and the second interface region, it is inferred that the interfacial strength between the tungsten carbide particles of the cemented carbide and the interfacial strength between the tungsten carbide particles and the binder phase are improved.

[0080] <Intermetallic Compounds and First Compounds> The cemented carbide of the first embodiment may not include an intermetallic compound (hereinafter also referred to as "first interalloy compound") consisting of two or more elements selected from the group consisting of the first element, cobalt, and tungsten, and a first compound consisting of at least one element selected from the group consisting of the first element, cobalt, and tungsten, and at least one element selected from the group consisting of carbon, nitrogen, and oxygen. Here, the first compound does not include tungsten carbide. This suppresses the decrease in strength of the cemented carbide.

[0081] Examples of the first intermetallic compound include Co2Si, Co3Si, and CoSi.

[0082] Examples of the first compound include Co3W3C and Co6W6C.

[0083] In the present disclosure, the fact that the cemented carbide does not contain either the first intermetallic compound or the first compound is confirmed by structural observation and EDX analysis of a cross section of the cemented carbide.

[0084] <Method of manufacturing cemented carbide> The cemented carbide of the first embodiment can be manufactured by carrying out the steps of preparing raw material powder, mixing, molding, sintering, the first cooling, HIP (Hot Isostatic Pressing) and the second cooling in the above order. Each step will be described below.

[0085] <Preparation process> The preparation step is a step of preparing a raw material powder of the cemented carbide. Examples of the raw material powder include tungsten carbide powder (hereinafter also referred to as "WC powder"), cobalt (Co) powder, a first element powder, and an alloy powder of the first element and cobalt. Examples of the first element powder include silicon (Si) powder, phosphorus (P) powder, germanium (Ge) powder, tin (Sn) powder, rhenium (Re) powder, ruthenium (Ru) powder, osmium (Os) powder, iridium (Ir) powder, and platinum (Pt) powder. Examples of the raw material powder include nickel (Ni) powder, niobium carbide (NbC) powder, carbide (Cb) powder, and carbide (Cc) powder. tantalum For example, TaC powder, titanium carbonitride (TiCN) powder, etc. can be prepared. These raw material powders can be commercially available. The average particle size of these raw material powders is not particularly limited and can be, for example, 0.5 to 5 μm. The average particle size of the raw material powder means the average particle size measured by the FSSS (Fisher Sub-Sieve Sizer) method. The average particle size is measured using a Fisher Scientific "Sub-Sieve Sizer Model 95" (trademark).

[0086] <Mixing process> The mixing step is a step of mixing the raw material powders prepared in the preparation step in a predetermined ratio. A mixed powder in which the raw material powders are mixed is obtained by the mixing step. The mixing ratio of the raw material powders is appropriately adjusted depending on the composition of the target cemented carbide.

[0087] The raw material powders can be mixed by a conventionally known mixing method such as an attritor, a ball mill, or a bead mill. Conventional known conditions can also be used for the mixing conditions. The mixing time can be, for example, 2 hours or more and 20 hours or less.

[0088] After the mixing process, the mixed powder may be granulated if necessary. By granulating the mixed powder, it becomes easier to fill the mixed powder into a die or mold during the subsequent molding process. For granulation, known granulation methods can be applied. For example, commercially available granulators such as spray dryers can be used.

[0089] <Molding Process> The molding process is a process of molding the mixed powder obtained in the mixing process into the shape of a cutting tool to obtain a molded body. The molding method and molding conditions in the molding process may adopt general methods and conditions and are not particularly limited.

[0090] <Sintering Process> The sintering process is a process of sintering the molded body obtained in the molding process to obtain a cemented carbide intermediate. The sintering conditions in Embodiment 1 are as follows. The molded body is heated to 1360°C at a heating rate of 30°C / min and held at 1360°C for 15 minutes.

[0091] <First Cooling Process> The first cooling process is a process of cooling the cemented carbide intermediate after the sintering process. Specifically, the cemented carbide intermediate is cooled to 800°C. The temperature reduction rate is -20°C / min.

[0092] <HIP Process> The HIP process is a process of performing HIP treatment on the cemented carbide intermediate after the first cooling process. The conditions of the HIP process are as follows. The cemented carbide intermediate is held at 200 MPa and 1310°C for 15 minutes.

[0093] <Second Cooling Process> The second cooling process is a process of cooling the cemented carbide intermediate after the HIP process. Specifically, the cemented carbide intermediate is cooled to 800°C. The temperature reduction rate is -30°C / min. Thereafter, slow cooling can be performed to obtain the cemented carbide of Embodiment 1. The temperature reduction rate during slow cooling may adopt general conditions and is not particularly limited.

[0094] <Features of the method for producing the cemented carbide according to the first embodiment> In the method for producing the cemented carbide of the first embodiment, the heating rate in the sintering step is 30° C. / min, which is higher than a general heating rate. The cooling rate in the second cooling step is −30° C. / min, which is higher than a general cooling rate. These conditions allow the production of the cemented carbide of the first embodiment, in which the binder phase contains 40 mass % or more of cobalt and at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum, and the first element is not segregated in the first interface region and the second interface region. The present inventors have found, through extensive research, that the cemented carbide of the present disclosure can be realized by adopting such a heating rate in the sintering step and a heating rate in the second cooling step.

[0095] [Embodiment 2: Cutting tool] A cutting tool according to one embodiment of the present disclosure (hereinafter also referred to as "embodiment 2") includes a cutting edge made of the cemented carbide of embodiment 1. In this disclosure, the cutting edge refers to a portion involved in cutting. More specifically, the cutting edge refers to a region surrounded by a cutting edge ridge and an imaginary surface that is 0.5 mm or 2 mm away from the cutting edge ridge toward the cemented carbide side.

[0096] Examples of cutting tools include cutting tools, drills, end mills, indexable cutting tips for milling, indexable cutting tips for turning, metal saws, gear cutting tools, reamers, taps, etc. In particular, as shown in Fig. 5, the cutting tool 10 of the second embodiment can exhibit excellent effects in the case of a small diameter drill for processing printed circuit boards. The cutting edge 11 of the cutting tool 10 shown in Fig. 5 is made of the cemented carbide of the first embodiment.

[0097] In the cutting tool of the second embodiment, the cemented carbide of the first embodiment may constitute the whole of these tools or may constitute a part of them. Here, "constituting a part" refers to a mode in which the cemented carbide of the first embodiment is brazed to a predetermined position of any substrate to form a cutting edge.

[0098] The cutting tool of the second embodiment may further include a hard film that covers at least a part of the surface of the substrate made of cemented carbide. The hard film may be made of, for example, diamond-like carbon or diamond.

[0099] The cutting tool of the second embodiment can be obtained by forming the cemented carbide of the first embodiment into a desired shape.

[0100] [Appendix 1] In the cemented carbide of the present disclosure, when adjacent tungsten carbide particles are a first tungsten carbide particle and a second tungsten carbide particle, a first interface is formed between the first tungsten carbide particle and the second tungsten carbide particle, The first interface region may be composed of a first A region within 1.2 nm from the first interface to the first tungsten carbide particle side, and a first B region within 1.2 nm from the first interface to the second tungsten carbide particle side.

[0101] [Appendix 2] In the cemented carbide of the present disclosure, a second interface is formed between adjacent tungsten carbide particles and a binder phase, The second interface region may be composed of a first C region that is located within 1.2 nm from the second interface toward the tungsten carbide particle side, and a first D region that is located within 1.2 nm from the second interface toward the binder phase side. EXAMPLES

[0102] The present embodiment will be described in more detail with reference to examples, although the present embodiment is not limited to these examples.

[0103] [Preparation of cemented carbide] Each sample of cemented carbide was prepared according to the following procedure. <Preparation process> As the raw material powders, WC powder (average particle size: 1 μm), Co powder (average particle size: 1 μm), first element powder, Ni powder (average particle size: 1 μm), TiCN powder (average particle size: 1 μm), TaC powder (average particle size: 1 μm), and NbC powder (average particle size: 1 μm) were prepared. As the first element powders, silicon (Si) powder (average particle size: 1 μm), phosphorus (P) powder (average particle size: 1 μm), germanium (Ge) powder (average particle size: 1 μm), tin (Sn) powder (average particle size: 1 μm), rhenium (Re) powder (average particle size: 1 μm), ruthenium (Ru) powder (average particle size: 1 μm), osmium (Os) powder (average particle size: 1 μm), iridium (Ir) powder (average particle size: 1 μm), and platinum (Pt) powder (average particle size: 1 μm) were prepared.

[0104] <Mixing process> A mixed powder was obtained by mixing the raw material powders for 10 hours using an attritor in the ratios shown in Table 1. The ratio (mass%) of each raw material powder shown in Table 1 is the ratio when the total mixed powder is taken as 100 mass%.

[0105] [Table 1]

[0106] <Forming process> The mixed powder was pressed to obtain a rod-shaped compact.

[0107] <Sintering process> The compact was heated to the temperature shown in the "Holding temperature" column at the heating rate shown in the "Heating rate" column of "Sintering step" in Table 2, and held at that temperature for the time shown in the "Holding time" column. This produced a cemented carbide intermediate.

[0108] <First cooling process> The cemented carbide intermediate body after the sintering step was cooled to 800°C at the temperature decreasing rate shown in the "Temperature decreasing rate" column of "First cooling step" in Table 2.

[0109] [Table 2]

[0110] <HIP Process> The cemented carbide intermediate after the first cooling process was subjected to HIP treatment. In the HIP treatment, the pressure described in the "Pressure" column of the "HIP Process" in Table 3 and the temperature described in the "Temperature" column were maintained for the time described in the "Time" column.

[0111] <Second Cooling Process> The cemented carbide intermediate after the HIP process was cooled to 800 °C at the cooling rate described in the "Cooling Rate" column of the "Second Cooling Process" in Table 3. Thereafter, it was slowly cooled to obtain the cemented carbide of each sample.

[0112]

Table 3

[0113] [Evaluation of Cemented Carbide] <Content Ratio (Volume %) of Tungsten Carbide Particles and Content Ratio (Volume %) of Bonding Phase in Cemented Carbide> The content ratio (volume %) of tungsten carbide particles and the content ratio (volume %) of the bonding phase of the cemented carbide of each sample were measured. The specific measurement method is as described in Embodiment 1. The results are shown in the "WC Particle Content Ratio" and "Bonding Phase Content Ratio" columns of the "Cemented Carbide" in Table 4. Further, the total of the content ratio of tungsten carbide particles and the content ratio of the bonding phase of the cemented carbide is shown in the "WC Particles + Bonding Phase Content Ratio" column of the "Cemented Carbide" in Table 4. In Table 4, it was confirmed that the cemented carbide with a "WC Particles + Bonding Phase Content Ratio" column of less than 100 volume % further contains TiCN, TaC, or NbC.

[0114] <Presence or Absence of First Intermetallic Compound and First Compound> In the cemented carbide of each sample, the presence or absence of the first intermetallic compound and the first compound was confirmed by observing the structure of the cross-section of the cemented carbide and EDX analysis. The results are shown in the "First Intermetallic Compound / First Compound" column of the "Cemented Carbide" in Table 4. When neither the first intermetallic compound nor the first compound was confirmed, it was marked as "None", and when at least one of the first intermetallic compound and the first compound was confirmed, it was marked as "Present".

[0115] <Cobalt content in cemented carbide> The cobalt content of the cemented carbide of each sample was measured. The specific measurement method is as described in embodiment 1. The results are shown in the "Co content" column of "Cemented carbide" in Table 4.

[0116] [Table 4]

[0117] <Cobalt content in binder phase> The cobalt content of the binder phase of each sample of cemented carbide was measured. The specific measurement method is as described in embodiment 1. The results are shown in the "Co content" column of "Binder phase" in Table 5.

[0118] <Type of the first element, and {M1 / (M1+M2)}×100> In the binder phase of the cemented carbide of each sample, the type of the first element and the percentage {M1 / (M1+M2)}×100 of the mass M1 of the first element relative to the sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt were measured. The specific measurement method is as described in embodiment 1. The results are shown in the "First element" column and the "{M1 / (M1+M2)}×100" column of "Binder phase" in Table 5. The samples marked with "-" in the "First element" column do not contain the first element.

[0119] <Existence or absence of segregation of the first element in the first interface region and the second interface region> In each sample of cemented carbide, the presence or absence of segregation of the first element in the first interface region and the second interface region was confirmed. The specific confirmation method is as described in embodiment 1. The results are shown in the "First interface region" and "Second interface region" columns of "Segregation of first element" in Table 5.

[0120] [Cutting test] A round bar made of cemented carbide of each sample was processed to prepare a drill for processing a printed circuit board (PCB (Printed Circuit Board) drill) with a cutting diameter of φ0.10 mm. Using the PCB drill, a hole was drilled in a commercially available printed circuit board for semiconductor packaging, and the hole position accuracy was evaluated. The printed circuit board used was a board with a thickness of 0.4 mm stacked on top of another. The conditions for the hole drilling were a rotation speed of 160 krpm, a feed rate of 2.0 m / min, and a drawing rate of 25 m / min. The hole position accuracy (ave+3σ(μm)) was measured when the number of holes drilled was 8000 (8000 hits). The measurement was performed three times, and the average hole position accuracy of the three measurements was calculated. The results are shown in the "Cutting test" column in Table 5. The smaller the hole position accuracy value, the better the hole position accuracy of the cutting tool and the longer the tool life.

[0121] [Table 5]

[0122] [Consideration] The cemented carbide and cutting tools of Samples 1 to 17 correspond to Examples. The cemented carbide and cutting tools of Samples 101 to 104 correspond to Comparative Examples. It was confirmed that the cutting tools of Samples 1 to 17 had better hole position accuracy and longer tool life than the cutting tools of Samples 101 to 104.

[0123] Although the embodiments and examples of the present disclosure have been described above, it is intended from the outset that the configurations of the above-described embodiments and examples may be appropriately combined or modified in various ways. The embodiments and examples disclosed herein are illustrative in all respects and should not be considered as limiting. The scope of the present invention is indicated by the claims, not by the embodiments and examples described above, and is intended to include the meaning equivalent to the claims and all modifications within the scope. [Explanation of symbols]

[0124] 1 Tungsten carbide particle, 2 binder phase, 3 cemented carbide, 4 interface, 10 cutting tool, 11 cutting edge.

Claims

1. A cemented carbide comprising a plurality of tungsten carbide particles and a binder phase, The cemented carbide contains 89 volume % or more of the tungsten carbide particles and the binder phase in total, The cemented carbide contains 1.5% by volume or more and 23% by volume or less of the binder phase, The binder phase contains 40% by mass or more of cobalt, the binder phase further comprises at least one first element selected from the group consisting of silicon, phosphorus, germanium, tin, rhenium, ruthenium, osmium, iridium, and platinum; The first element is not segregated in a first interface region between adjacent tungsten carbide particles, and the first element is not segregated in a second interface region between adjacent tungsten carbide particles and the binder phase; Here, the absence of segregation of the first element in the first interface region between the adjacent tungsten carbide particles means that, in four or more of the five first graphs obtained based on the five first TEM images shown below, A / B measured in the following steps (a1) to (f1) is less than 3: (a1) obtaining five first TEM images of a cross section of the cemented carbide; (b1) performing line analysis using an energy dispersive X-ray analyzer attached to a TEM in a direction perpendicular to an extension direction of a first interface between adjacent first tungsten carbide particles and second tungsten carbide particles in each of the first TEM images and in a direction from the first tungsten carbide particles toward the second tungsten carbide particles, to obtain a first graph measuring distributions of cobalt, tungsten and the first element; (c1) In the first graph, a first A region in which the distance from the first interface to the first tungsten carbide particle side is within 1.20 nm, a first B region in which the distance from the first interface to the second tungsten carbide particle side is within 1.20 nm, a second A region in which the distance from the first interface to the first tungsten carbide particle side is 1.50 nm or more and 3.50 nm or less, and a second B region in which the distance from the first interface to the second tungsten carbide particle side is 1.50 nm or more and 3.50 nm or less, are identified. (d1) calculating an average B atomic % of the content of the first element in a baseline region consisting of the second A region and the second B region in the first graph; (e1) measuring a maximum value A atomic % of the content of the first element in the first interface region formed of the first A region and the first B region in the first graph; (f1) calculating a ratio A / B of the maximum value A to the average B; Here, the fact that the first element is not segregated in the second interface region between the tungsten carbide particles and the binder phase adjacent to each other means that, in four or more of the five second graphs obtained based on the five second TEM images shown below, C / D measured in the following steps (a2) to (f2) is less than 3: (a2) obtaining five second TEM images of a cross section of the cemented carbide; (b2) performing line analysis in each of the second TEM images using an energy dispersive X-ray analyzer attached to the TEM in a direction perpendicular to the extension direction of second interfaces between the adjacent tungsten carbide particles and the binder phase and in a direction from the tungsten carbide particles toward the binder phase, to obtain a first graph measuring the distribution of cobalt, tungsten and the first element; (c2) In the second graph, a first C region in which the distance from the second interface to the tungsten carbide particle side is within 1.20 nm, a first D region in which the distance from the second interface to the binder phase side is within 1.20 nm, a second C region in which the distance from the second interface to the tungsten carbide particle side is 1.50 nm or more and 3.50 nm or less, and a second D region in which the distance from the second interface to the binder phase side is 1.50 nm or more and 3.50 nm or less are identified. (d2) calculating an average D atomic % of the content of the first element in a baseline region consisting of the second C region and the second D region in the second graph; (e2) measuring the maximum value C (atomic %) of the content of the first element in the second interface region in the second graph; (f2) Calculating the ratio C / D of the maximum value C to the average D, the cemented carbide.

2. 2. The cemented carbide according to claim 1, wherein in the binder phase, a percentage of the mass M1 of the first element relative to a sum M1+M2 of the mass M1 of the first element and the mass M2 of cobalt, {M1 / (M1+M2)}×100, is 1% or more and 6% or less.

3. The cemented carbide is an intermetallic compound consisting of two or more elements selected from the group consisting of the first element, cobalt and tungsten; and The first element does not include a first compound consisting of at least one element selected from the group consisting of cobalt and tungsten, and at least one element selected from the group consisting of carbon, nitrogen, and oxygen, 3. The cemented carbide of claim 1 or claim 2, wherein the first compound does not include tungsten carbide.

4. A cutting tool having a cutting edge made of the cemented carbide according to claim 1 or 2.

Citation Information

Patent Citations

  • Method for preparing hard alloy product containing surface low-cobalt layer

    CN103774026A

  • Cemented carbide-made miniature drill excellent in breaking resistance

    JP2010012552A

  • Cemented carbide alloy and coated cemented carbide alloy

    WO2015178484A1

  • Tungsten carbide powder, tungsten carbide-cobalt metal composite powder, and cemented carbide

    WO2019123764A1

  • Hyperfine-grained cemented carbide

    JP2004131769A